Synthesis of Ga-Doped ZnO Nanoparticles by Solvothermal Method - Huynh, Thi Bich Hao; Nguyen, Thi Thu Hien; Duong, Thanh Tung; Nguyen, Huu Dung; Trinh, Xuan Anh; Nguyen, Duy Cuong (Old Journal, 2019)
In this paper, Ga-doped ZnO nanoparticles (GZO NPs) are synthesized by the solvothermal method from different precursors and with different Ga doping concentrations (0%, 1%, 3%, 5%, 7% and 9%) at the same temperature of 250 °C in the oleylamine solvent. The structural, morphological and optical characteristics were studied by X-ray diffraction, field-emission scanning electron microscope and UV–Vis absorption spectra. Particle size and morphology are strongly influenced by changes in precursor Ga and Ga. The concentration of doping Ga also affects the morphology, structure and optical properties of GZO NPs. When Ga doping concentration increased from 0 to 9%, the nanoparticle size changed in the range of 19–36 nm. GZO NPs have relatively high transmittance. Among the samples with different doping concentrations, the nanoparticles with 5% Ga doping showed the highest transmittance, 85% at the wavelength of 550 nm. This suggests that these nanoparticles are promising to make nanocomposite films applied in transparent conductive electrodes.